Structural percolation controls the precipitation kinetics of colloidal calcium–silicate–hydrate gels. (3rd June 2019) - Liu, Han; Tang, Longwen; Krishnan, N M Anoop; Sant, Gaurav; Bauchy, Mathieu
Abstract: As out-of-equilibrium materials, the structure and properties of colloidal gels are largely controlled by the history of their precipitation. However, the role played by the gel microstructure in controlling the kinetics of its precipitation remains unclear. Here, based on coarse-grained mesoscale simulations, we investigate the mechanism governing the precipitation of calcium–silicate–hydrate (C–S–H) gels—the binding phase of concrete. We demonstrate that both the kinetics and thermodynamics of C–S–H's precipitation are closely correlated to the percolation of its underlying microstructure. Based on these results, we show that the critical packing density at which the gel is percolating is governed by the balance between the size and the shape of the C–S–H clusters forming upon precipitation. Overall, this study deciphers the linkages between gel microstructure and precipitation kinetics, which is key to design novel gel phases with tailored microstructure and properties.